Forage Sorghum Silage Cost-Return Budget in South Central Kansas - Dumler, Troy J.; Duncan, Stewart R. (My University, 2003)
The cost-return projection estimates the cost of producing forage sorghum silage in south central Kansas.
MF648_2003_10
Keywords: MF648; Economics; Crops; MF